ZAKAT KNOWLEDGE, INSTITUTIONAL TRUST, AND PAYMENT INTENTION: THE MODERATING ROLE OF DIGITAL COMPETENCY - Imama Zuchroh; Muh. Prasesa Widodo Amrullah; Oktavia Khoirotun Nisa (RADJA PUBLIKA, 2025)
This study examines the influence of zakat literacy and trust on zakat payment intention, with digital literacy serving as a moderating variable. The research employs a quantitative approach using Structural Equation Modeling (SEM) with SmartPLS analysis. Data were collected from 35 respondents through a structured questionnaire using a 5-point Likert scale. The study variables include zakat literacy (LZ), trust (KP), zakat payment intention (MZ), and digital literacy (LD) as moderating variable. The measurement model evaluation shows satisfactory construct validity and reliability with all factor loadings exceeding 0.7, composite reliability values above 0.8, and AVE values above 0.5. The structural model reveals that zakat literacy significantly influences zakat payment intention (β = 0.342, p < 0.05), while trust demonstrates an even stronger effect (β = 0.458, p < 0.01). Digital literacy significantly moderates both relationships, strengthening the zakat literacy-intention relationship from 0.342 to 0.598 for high digital literacy individuals, and enhancing the trust-intention relationship from 0.458 to 0.647. The model explains 67.3% of variance in zakat payment intention. The findings contribute to understanding factors that enhance zakat collection effectiveness in the digital era, providing practical implications for zakat institutions to develop digital-based strategies for improving zakat collection and management. Keywords: zakat literacy, trust, payment intention, digital literacy, moderation effect, SmartPLS